EFEKTIVITAS EKSTRAKURIKULER TAḤFIẒ AL QUR’AN PADA SISWA KELAS X KEAGAMAAN DI MADRASAH ALIYAH MUHAMMAD BASIUNI IMRAN SAMBAS TAHUN PELAJARAN 2021-2022 - Yusril Chandra (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
This study is motivated by the addition of high scool students who are not fluent in reading the Qur’an but have joined the tahfiz al-qur’an program. The purpose of this research is to find out: (1) the method of memorizing al-qur’an used by students; (2) factors that affec student memorization. The approach used in this research is qualitative with the type of case study. The data collection techniques used are interviews, observation and decumentation. Data abalysis was carriedout with the stages of reduction, display and verification. The data validity test was carried out using triangulation and member check techniques. The results showed that:1) the memafa method used by students consisted of: (a) wahdah method;(b) sima’i method; (c) bin-nazar method. 2) supporting factors in memorizing the Qur’an for class X Religious students consist of: (a) intention; (b) fluency; (c) motivation. While the inhibiting factors in memorizing the Qur’an for class X Religious students consist of: (a) laziness; (b) inconsistency in discipline; (c )friendship; (d) sin; (e) love of the world.